Pediatric Germ Cell Tumors: A Developmental Perspective - Joshua L. Pierce; A. Lindsay Frazier; James F. Amatruda (Advances in Urology, 2018)
Germ cell tumors (GCTs) arising in infants, children, and adolescents present a set of special challenges. GCTs make up about 3% of malignancies in children aged 0–18 and nearly 15% of cancers in adolescents. Epidemiologic and molecular evidence suggests that GCTs in young children likely represent a distinct biologic group as compared to GCTs of older adolescents and adults. Despite this difference, pediatric GCTs are typically treated with cisplatin-based multiagent regimens similar to those used in adults. There is evidence that children are particularly vulnerable to late effects of conventional therapy, including ototoxicity, pulmonary abnormalities, and secondary malignancies, motivating the search for molecular targets for novel therapies. Evidence is accumulating that the genes and mechanisms controlling normal germ cell development are particularly relevant to the understanding of germ cell tumorigenesis. Perturbations in the epigenetic program of germ cell differentiation, with resulting effects on the regulation of pluripotency, may contribute to the marked histologic variability of GCTs. Perturbations in the KIT receptor signaling pathway have been identified via next-generation sequencing studies and in genome-wide association studies of testicular cancer susceptibility. Here, we review these and other biological insights that may fuel further translational and clinical research in childhood GCTs.